1988
DOI: 10.1136/adc.63.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Arm fat and muscle areas in infancy.

Abstract: Jelliffee pointed out that the cross sectional arm areas represent better estimates of the relative contribution of fat and muscle to the total arm area than mid arm circumference and triceps skinfold.4To our knowledge there is no report of these arm areas measured at birth and then measured regularly throughout the first year of life. Therefore the first aim of this study was to report these mid arm fat and muscle areas from measurements collected prospectively in a population of 100 infants and to provide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…The derived anthropometric values using equations based on the assumption that various regions of the body and extremities are cylinders (10,11) have some theoretical advantages compared with the use of simple ratios. However, this assumption is likely an oversimplification of the anatomy and is consistent with the reports of their poor agreement with body composition measured by reference laboratory methods including total body electrical conductivity (36) or DXA (37) in infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The derived anthropometric values using equations based on the assumption that various regions of the body and extremities are cylinders (10,11) have some theoretical advantages compared with the use of simple ratios. However, this assumption is likely an oversimplification of the anatomy and is consistent with the reports of their poor agreement with body composition measured by reference laboratory methods including total body electrical conductivity (36) or DXA (37) in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports indicated that regional anthropometry or the ratios and formulas derived from these measurements are good predictors of fetal growth and metabolic disturbances noted in neonates who are over-or undergrown for the duration of gestation (7)(8)(9). These refinements of regional anthropometry are thought to reflect more specific body composition, namely lean mass and fat mass (10,11), which allows assessment of the quality of growth such as the extent of energy, fat and protein deposition, and the potential mechanism for disturbed metabolism in infants with abnormal in utero growth.…”
mentioning
confidence: 99%
“…For the calculation of the arm muscle area, the conventional assumptions are that: (1) the mid-arm is cylindrical; (2) the subcutaneous fat is a concentric ring evenly distributed around the muscle; (3) that fat thickness is half the TSF; (4) that the muscle compartment is circular; and (5) that the muscle includes the humeral diameter. Any variation in bone diameter is not taken account [1,3,5]. Possible source of error using conventional assumptions is the variable tissue compression relative to differences in the skin tension when measuring TSF [6].…”
Section: Introductionmentioning
confidence: 99%
“…Standards for full-term and preterm neonates have also been reported recently [3,4]. These values are extrapolated from equations derived from mid-arm circumference (MAC) and tricipital skinfold thickness (TSF) [1,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, z-scores were calculated for TSF, upper arm circumference and arm muscular area using reference values from Frisancho 25 for children more than 1 year old and values from Sann et al 26 for children less than one.…”
Section: Anthropometrymentioning
confidence: 99%